2011
DOI: 10.1016/j.humimm.2011.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Studying the genetic predisposing factors in the pathogenesis of acne vulgaris

Abstract: A B S T R A C TAcne is one of the most common dermatologic diseases in the developed regions of the world, affecting a large percentage of the population. Despite the great improvement in the number and quality of studies of the molecular etiology of this disease in the past 3 decades, the detailed molecular pathogenesis and the cause of the large individual variations in severity of skin symptoms remain unknown. The roles of genetic inheritance and special genetic susceptibility and protective factors have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 89 publications
2
38
0
5
Order By: Relevance
“…We additionally found that CBD also prevented the "pro-acne" LA-T combination from elevating the expression of TNFA ( Figure 3A), a key cytokine in the pathogenesis of acne vulgaris (2,(24)(25)(26)(27)(28)(29)(30). These data suggested that CBD may exert antiinflammatory actions on human sebocytes (as had already been demonstrated for CBD in several other experimental models, such as diabetes, rheumatoid arthritis, etc.)…”
Section: Cbd Normalizes "Pro-acne Agent"-induced Excessive Lipid Syntsupporting
confidence: 80%
See 1 more Smart Citation
“…We additionally found that CBD also prevented the "pro-acne" LA-T combination from elevating the expression of TNFA ( Figure 3A), a key cytokine in the pathogenesis of acne vulgaris (2,(24)(25)(26)(27)(28)(29)(30). These data suggested that CBD may exert antiinflammatory actions on human sebocytes (as had already been demonstrated for CBD in several other experimental models, such as diabetes, rheumatoid arthritis, etc.)…”
Section: Cbd Normalizes "Pro-acne Agent"-induced Excessive Lipid Syntsupporting
confidence: 80%
“…Moreover, CBD also normalized LPS-induced IL1B and IL6 expression ( Figure 3B) (expression of these 2 cytokines was found not to be modulated by 24-hour LA-T or LTA treatment; data not shown). Taken together, these results strongly suggest that CBD's universal sebostatic action is accompanied by substantial antiinflammatory effects, which would be very much desired in the clinical treatment of acne vulgaris (1,2,(24)(25)(26)(27)(28)(29)(30) ] IC (Supplemental Figure 10) and the lipid-lowering action of the TRPV4-specific activator GSK ( Figure 5E). Collectively, these data unambiguously confirm that CBD activates TRPV4 and that this ion channel selectively mediates its lipostatic action.…”
Section: Cbd Normalizes "Pro-acne Agent"-induced Excessive Lipid Syntmentioning
confidence: 81%
“…Although its role is intensely debated, there is increasing evidence that P. acnes is a powerful inducer of inflammation and that it plays a crucial role in the pathogenesis of acne in genetically disposed individuals (4,8,18,30). The apparent contradiction with its role as a ubiquitous and predominant skin commensal may be explained by strain-dependent differences in pathogenic potential (11,15,21,22,25,26,33).…”
mentioning
confidence: 99%
“…Az életmód szerepe az acne kialakulásában Számos közlést találunk az irodalomban, ami arra utal, hogy a természetes körülmények között élő népcsoportok-nál, mint az eszkimóknál vagy a kitava törzs tagjainál az acne ismeretlen, vagyis a betegség a nyugati típusú társa-dalmak egyik jellegzetessége lehet (16). Logikus a követ-keztetés hogy a háttérben az eltérő életmód, a részben azzal összefüggésben álló hormonális tényezők, valamint eltérő bőr mikroflóra állhat, melyek lehetséges szerepéről rendelkezésre álló ismereteinket részletesebben is bemutatjuk.…”
Section: Az Acnéra Ható Nem Sejtszintű Faktorokunclassified
“…Számolni kell emellett a táplálkozás és esetleges egyéb betegségek hatásával is, melyek szisztémás és sejtspecifikus hatásainak megismerése csak most kezdő-dött el az acne kontextusában (16,48). Ez a komplexitás és az igazolt "kulcsfaktorok" hiánya jelenik meg és okoz nehézséget a megfelelő terápiás stratégiák kialakításá-ban is, és (egyenlőre) irányvonalak vannak mintsem cél-zott terápia, szemben például a pikkelysömörrel.…”
Section: Az Eredményekben Rejlő Terápiás Perspektívákunclassified